Pelanggaran di Wilayah ALKI yang Dilakukan oleh Kapal Asing - Vondaal Vidya Hattu (Ridwan Institute, 2021)
Foreign vessels that will cross the Indonesian archipelago can use their rights to pass through the ALKI (Indonesian Archipelago Sea Lanes). However, these foreign vessels are not allowed to pass through the entire ALKI area but can only pass through the three ALKI areas according to the route that has been determined. With a large number of foreign vessels passing through the ALKI area, it can also indirectly lead to various violations that often occur in the ALKI area committed by foreign vessels, such as cases of illegal immigrants, smuggling of weapons, smuggling of narcotics and drugs, marine pollution, illegal fishing included protected fishing, illegal inspection activities, human trafficking, customs, and various other violations. This research aims to examine violations in the ALKI area committed by foreign vessels. This study uses a normative juridical research method. The results showed that violations in ALKI area committed by foreign vessels were generally related to the right of peaceful passage and the right of archipelagic passage. This research concludes that the Indonesian government established an institution and ratified laws and regulations to minimize violations in the ALKI area committed by foreign vessels.